Can philosophy be a way of living? - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2006)
Philosophy can become a way of living. Sometimes as a purpose, sometimes as a kind of passion. Like every passion, it requires devotion. It requires time - for thinking, reading, learning, discussing... In this paper some remarks about making philosophy a way of living are sketched.